Diagnosis of spontaneous hyperadrenocorticism in dogs. Part 2: Adrenal function testing and differentiating tests. (October 2019) - Bennaim, Michael; Shiel, Robert E.; Mooney, Carmel T.
Highlights: The diagnosis of hyperadrenocorticism (HAC) is based on multiple pieces of information rather than the result of one test. Most studies evaluating the diagnostic performance of adrenal function tests in the diagnosis of HAC have shortcomings. Recently described interpretations of adrenal function test results may provide additional diagnostic information. Abstract: Hyperadrenocorticism is a relatively common endocrine disorder in dogs that has been extensively described. However, its diagnosis remains challenging because there is no true reference standard test, and a myriad factors can affect the diagnostic performance of the commonly used adrenal function tests. Ultimately, the diagnosis is based on a combination of signalment, history and clinical findings, and a variety of diagnostic test results. The second part of this review aims to appraise available data on diagnostic performance of adrenal function tests in naturally occurring canine hyperadrenocorticism.